RISK MANAGEMENT MODEL FOR RAW MATERIAL PROCUREMENT AND PRODUCTION PLANNING IN THE COFFEE AGROINDUSTRY: A CASE STUDY IN KALIBARU, BANYUWANGI - Khotijah; Taufik Djatna; Marimin (Jurnal Teknologi Industri Pertanian, 2025)
The coffee agroindustry encounters significant risks due to its intricate business processes and the involvement of multiple stakeholders. These risks, particularly in raw material procurement and production planning, threaten business sustainability and include inconsistent raw material quality and quantity, fluctuating prices, limited resources, and inefficiencies in decision-making. This study analysed business processes, identifies risks, and develops a risk mitigation model for the coffee agroindustry in Kalibaru, Banyuwangi. Business process analysis employed descriptive methods focusing on supply chain mechanisms and drivers, complemented by supply chain management metrics. Risk management utilized the House of Risk (HOR) Phase 1 and 2 framework. Results revealed a refined business process model emphasizing efficiency and integration, alongside 20 risk events and 20 risk sources in both procurement, and production planning. Eleven priority risk sources were identified for procurement, and ten for production, forming the basis for targeted mitigation strategies. Key mitigation actions include training farmers in Good Agricultural Practices (GAP), partnering with research institutions for procurement and implementing preventive maintenance of processing equipment for production. These strategies enhance resource management and industry competitiveness. Keywords: business process, coffee agroindustry, risk mitigation, procurement planning, production planning